Lean performance evaluation of dairy cow farming processes with mathematical model development - Thalmeiner Gergő; Gergo Talmeiner; Gáspár Sándor; Sandor Gaspar; Tóth Márk (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2023)
Abstract. Management sciences, especially controlling, are undergoing extensive changes. Various mathematical-statistical and IT solutions help organizations develop their systems and extract relevant information from data structures, thereby supporting effective decision-making and organizational operations. Agriculture is a special sector, but management functions apply here too, and modern tools and methods support the implementation of efficient operations. Dairy farming is a particularly important sector in agriculture, where controlling systems are developed in response to special requirements. The controlling activity of the sector is significantly influenced by the development of digitalization, which has resulted in the monitoring of processes and organizational performance evaluation becoming more extensive and detailed. Lean management is also an excellent method for increasing the efficiency of processes and organizational performance in the agricultural sector, which can be used to optimize processes, identify unnecessary activities and ensure appropriate task control. In this way, controlling systems must take into account the importance of lean management and contribute to the performance evaluation of organizational lean. In our study, we develop a lean performance evaluation model through an extended case study, which is suitable for evaluating the lean performance of the examined dairy farm. We used a fuzzy triangular function to evaluate the performance of enterprises, which represents the value of the given parameter with a triangular distribution. With dynamically growing and usable data, the model is able to provide continuous feedback on organizational lean operation and possible intervention points.

A menedzsment tudományok, különösen a controlling, széleskörű változásokon mennek keresztül. Különféle matematikai-statisztikai és informatikai megoldások segítik a szervezeteket abban, hogy fejlesszék rendszereiket és releváns információkat vonjanak ki az adatstruktúrákból, támogatva ezzel a hatékony döntéshozatalt és szervezeti működést. A mezőgazdaság speciális ágazat, ám a menedzsment funkciók itt is érvényesülnek, a modern eszközök és módszerek támogatják a hatékony működés megvalósítását. A tejelő tehenészet különösen fontos ágazat a mezőgazdaságban, ahol a controlling rendszerek a speciális követelményekre válaszolva fejlődnek. Az ágazat controlling tevékenységét a digitalizációs fejlődés jelentős mértékben befolyásolja, amely hatására a folyamatok nyomon követése és a szervezeti teljesítményértékelés monitoringozása kiterjedtebbé és részletesebbé vált. A folyamatok hatékonyságának és a szervezeti teljesítmény növelésére az agrár szektorban is kiváló módszer a lean menedzsment, amely alkalmazásával optimalizálhatók a folyamatok, azonosíthatók a felesleges tevékenységek és biztosítható a megfelelő feladatkontroll. Ezáltal a controlling rendszereknek figyelembe kell venniük a lean menedzsment jelentőségét és hozzá kell járulniuk a szervezeti lean teljesítményértékeléséhez. Tanulmányunkban egy kiterjesztett esettanulmányon keresztül fejlesztünk egy lean teljesítményértékelő modellt, amely alkalmas a vizsgált tejelő tehenészet lean teljesítményének értékelésére. Fuzzy háromszög függvényt alkalmaztunk a vállalkozások teljesítményének értékelésére, amely az adott paraméter értékét egy háromszög alakú eloszlással reprezentálja. A dinamikusan növekvő és felhasználható adatokkal a modell képes folyamatos visszajelzést adni a szervezeti lean működésről és a lehetséges beavatkozási pontokról.

Резюме. Науки управління, особливо контролінг, зазнають великих змін. Різноманітні математико-статистичні та ІТ-рішення допомагають організаціям розвивати свої системи та отримувати відповідну інформацію зі структур даних, таким чином підтримуючи ефективне прийняття рішень та організаційну діяльність. Сільське господарство – це особлива галузь, але і тут діють функції управління, а сучасні засоби та методи сприяють здійсненню ефективної діяльності. Молочне скотарство є особливо важливою галуззю сільського господарства, де системи контролю розробляються відповідно до особливих вимог. На контролінгову діяльність сфери суттєво впливає розвиток діджиталізації, що призвело до більш масштабніших та детальніших процесів моніторингу та оцінки ефективності управління. Бережливе управління також є важливим методом підвищення ефективності процесів та організаційної ефективності в аграрному секторі, що можна використовувати для оптимізації процесів, виявлення непотрібних дій і забезпечення належного контролю завдань. Таким чином, системи контролінгу повинні враховувати важливість ощадливого менеджменту та сприяти оцінці продуктивності організаційної ощадливості. У даному дослідженні представлено модель оцінки ефективності ощадливого виробництва за допомогою розширеного прикладу, який підходить для оцінки продуктивності ощадливого виробництва досліджуваної молочної ферми. Завдяки динамічно зростаючим і придатним для використання даних, модель здатна забезпечувати безперервний зворотний зв’язок щодо ефективної роботи організації та можливих точок розвитку та втручання.
Оцінка бережливості процесів вирощування молочних корів із розробкою математичної моделі
A tejelő tehenek nevelési folyamatainak takarékosságának értékelése matematikai modellezés segítségével
https://aab-economics.kmf.uz.ua/aabe/issue/view/3
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00012366
Keywords: lean management; lean controlling; agribusiness; performance evaluation; fuzzy logic